Staying the Course: The Option of Doing Nothing and Its Impact on Postchoice Persistence. (March 2014) - Schrift, Rom Y.; Parker, Jeffrey R.
Individuals regularly face adversity in the pursuit of goals that require ongoing commitment. Whether or not individuals persist in the face of adversity greatly affects the likelihood that they will achieve their goals. We argue that a seemingly minor change in the individual's original choice set—specifically, the addition of a no-choice option—will increase persistence along the chosen path. Drawing on self-perception theory, we propose that choosing from a set that includes a no-choice (do nothing) option informs individuals that they both prefer the chosen path to other paths and that they consider this path alone to be worth pursuing, an inference that cannot be made in the absence of a no-choice option. This unique information strengthens individuals' commitment to, and increases their persistence on, their chosen path. Three studies employing incentive-compatible designs supported our predictions and ruled out several rival accounts.